ANALISIS FINANSIAL DAN SENSITIVITAS PETERNAKAN AYAM BROILER PT. BOGOR ECO FARMING, KABUPATEN BOGOR - Abel Gandhy; Dicky Sutanto (Universitas Tribhuwana Tunggadewi, 2017)
The purpose of this paper is to analyze the feasibility of PT Bogor Eco Farming based on Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PP) and Break-even Point (BEP). Futhermore, sensitivity analysis use to know the impact due the decrease of chicken broiler selling price and a decrease in production. The research revealed the NPV is Rp 700.893.045, IRR is 37% and Pay Back Period (PP) is 2 years and 1 month. Sensitivity analysis conclude that farm business still feasible if chicken broiler selling price fell 5% and not feasible when chicken production decreased 10%.